Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inquiri Terbimbing Pada Materi Protista Kelas X SMA Negeri 1 Talibura - Novensia Yulinda; Yohanes Nong Bunga; Mansur S (Peneliti.net, 2023)
In the learning process, students are less encouraged to develop thinking skills. Students are directed to the ability to memorize material, are led to remember and hoard various information without understanding the material and lack of supporting facilities. LKPD can help students to learn both independently and in groups to improve thinking skills. This study aims to develop LKPD design and test the validity of LKPD media based on guided inquiry on protist material. This research was conducted at SMA Negeri 1 Talibura. The type of research is in the form of development by following the five stages (MANTAP) model which consists of 3 stages, namely the preliminary research stage, model development, and model validation. The products developed were validated by material, media and language experts and obtained an average value of 100% from material experts, 93% from linguists and 87.5% from media experts. Based on the validator's results, the guided inquiry-based LKPD developed is very feasible to be used as a learning medium in schools